PENGARUH SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) (Studi Kasus Pada Seluruh Sekolah Menengah Pertama Penerima Dana BOS di Kota Serang) - Fauzan Fadhlurrahman, - (2019)
This study aims to determine the influence of the internal control system on the quality of the financial statements in all junior high schools receiving BOS funds in Serang. The total sample used in this study are 61 schools. The original sample determined by researcher were 76 schools, however, as many as 13 schools did not return the questionnaire and 2 other schools in 2019 were declared bankrupt.This research used saturated sampling. The data in this reseach is collected by distributing questionnaires. Hypothesis testing is conducted by using SEM-PLS with the help of SmartPLS 3.0 software. The results obtained from this research shows that the internal control system affects the quality of the financial statements of BOS funds in junior high schools receiving BOS funds in Serang City.